PABRIK 2-ETIL HEKSANOL DARI PROPILEN DAN GAS SINTESIS KAPASITAS 200.000 TON /TAHUN - , EKO WAHYUDI, Muslikhin Hidayat , S.T., M.T., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Production of 2-ethyl hexanol is through three stages of reaction. The first, propylene and synthesis gas is reacted in the oxo reactor with a solution of rhodium catalyst at a pressure of 50 atm and a temperature of 115 °C to form n-butanal as the main product, and i-butanal as a byproduct. The second, n-butanal is reacted in the aldol reactor to form 2-ethyl hexenal at a pressure of 3.2 atm and a temperature of 110 °C. The next stage is process of hydrogenation of 2-ethyl hexenal become 2-ethyl hexanol with Raney Nickel catalyst at a pressure of 25 atm and a temperature of 130 °C. This plant produces 2-ethyl hexanol as much as 200.000 tons / year with a purity of 98%. While the addition of i-butanal 44,24% and n-butanal 41,95%. The plant needs 156.906,79 tonnes/year of propylene, and synthesis gas 120.773,27 tonnes/year of raw materials. The utilities needs water at the rate 532,7049 m 3 /hr, fuel gas at the rate of 5,7392 m 3 /hr, power 2.973,3965 kVA and air for instrumentation and process at the rate of 70,2240 m 3 /hr. The 2-ethyl hexanol plant will be built in Cikampek, West Java. It needs 7 hectare area and 229 employees. Based on economic analysis, the fixed capital of 2-ethyl hexanol plant is Rp 2.167.346.762.909,24 and US$ 238.169.973,95, and working capital of 2-ethyl hexanol plant is Rp 2.401.402.501.288,88. The manufacturing cost of 2-ethyl hexanol plant is Rp 2.885.960.713.383,24, and the general expenses of 2-ethyl hexanol plant is Rp. 271.550.424.979,97. The result of economic analysis shows that the 2-ethyl hexanol plant produces profit before taxes Rp 1.007.104.817.484,70 and profit after taxes Rp 503.552.408.742,35. The value of Percent Return of Investment (ROI) before taxes is 46,47% and after taxes is 23,23%. The value of Pay Out Time (POT) before taxes is 1,77 years and after taxes is 3,01 years. The value of Break Even Point (BEP) is 43,68%, Shut Down Point (SDP) is 22,93% ,and Discounted Cash Flow Rate of Return (DFCRR) is 14,03%. Based on data above, The 2-ethyl hexanol Plant from propylene and synthesis gas with 200.000 tonnes/year capacity is potential for furtherevaluation.